Agricultural Aviation Security - Wolf, Robert E.; Gardisser, Dennis R. (My University, 2002)
This publication is a checklist for small airport facilities, aircraft and other agricultural aviation security. It is for proper planning and good security measures.
EP111_2002_03
Keywords: EP111; Equipment and Structures; aviation; health and safety; EP